Internal Quality of Mojosari Duck Eggs by Soaking in Bandotan Plant Solution (Ageratum Conyzoides L) as a Natural Preservative - Krisnaningsih, Aju Tjatur Nugroho; Setiawan, Dwi Agus; Leondro, Henny (Faculty of Agriculture, 2025)
The purpose of this study was to determine the effect of soaking in a solution of Bandotan plants (Ageratum conyzoides L) on the quality of Mojosari duck eggs. This research method was a laboratory experiment with a Completely Randomized Design (CRD) consisting of five treatments and three replications. The concentration of egg soaking in a solution of Bandotan plants was 0% (T0), 10% (T1), 20% (T2), 30% (T3), and 40% (T4). The research data were analysed using Analysis of Variance (ANOVA), if there were differences between treatments, then continued with Duncan's Multiple Range Test. The results showed that soaking in a solution of Bandotan plants gave a significant difference (P0.05) to the shrinkage of egg weight, egg cavity height, egg yolk index, egg white index, haugh unit (HU). The value of egg weight shrinkage from the smallest to the largest as follows 6.87% (T2) and 12.14% (T0). Egg cavity height: 4.41 (T2) and 10.31 (T0). Egg yolk index: 0.12 (T0) and 0.46 (T2). Egg white index: 0.043 (T0) and 0.101 (T2). Haugh unit (HU): 52.20 (T0) and 80.37 (T2). Based on the results of this study, it can be concluded that soaking Mojosari duck eggs in a 20% solution of Bandotan (A. conyzoides L) for 12 hours was the most effective concentration for maintaining internal egg quality during 21 days of storage at room temperature.